Sustainable solvents for β-diketone extraction from wheat straw wax and their molecular self-assembly into nano-structured tubules for hydrophobic coatings. Issue 4 (17th January 2023) - Noppawan, Pakin; Sangon, Suwiwat; Chatsiri, Petcharaphorn; Khunmood, Nutnicha; Aintharabunya, Suphatta; Supanchaiyamat, Nontipa; Hunt, Andrew J.
Abstract : 2, 2, 5, 5-Tetramethyloxolane (TMO) and 2, 5-diethyl-2, 5-dimethyloxolane (DEDMO) were utilized as sustainable solvents for β-diketone extraction and its molecular self-assembly into nano-structured tubules for hydrophobic coatings. Abstract : Nonpolar, nonperoxide forming, sustainable and potentially bio-based solvents, namely 2, 2, 5, 5-tetramethyloxolane (TMO) and 2, 5-diethyl-2, 5-dimethyloxolane (DEDMO), were utilized as an alternative to toxic petroleum-based hydrocarbon solvents for extraction of hentriacontane-14, 16-dione from waste wheat straw waxes. This work is the first to report the application of DEDMO as a solvent for the extraction of natural products. The sustainable methodology developed in this research provided considerable advantages over previously reported systems in terms of high extraction yields, excellent selectivity towards the β-diketones and low amounts of waste generated. DEDMO provided the highest recovery yield for all the sustainable solvents investigated, recovering 23.7% of the wax (which is a 68.8% yield of the β-diketone). The extracted lipophilic hentriacontane-14, 16-dione was utilised in combination with the sustainable solvents TMO or DEDMO to facilitate the creation of highly hydrophobic coatings. Moreover, the use of DEDMO was found to aid in the self-assembly of nano-structured tubule formation of both the unrefined wax and isolated β-diketone. Green metric evaluation using process mass intensity (PMI), E-factor, solvent intensity (SI), and water intensity (WI) demonstrated that the described extraction procedure for hentriacontane-14, 16-dione was highly sustainable and safer than the previous methodology. This sustainable manufacturing process may create the potential to valorise agricultural wastes as part of a holistic biorefinery.